2019
DOI: 10.1101/766170
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Visual properties of human retinal ganglion cells

Abstract: 25The retinal output is the sole source of visual information for the brain. Studies in non-primate 26 mammals estimate that this information is carried by several dozens of retinal ganglion cell 27 types, each informing the brain about different aspects of a visual scene. Even though 28 morphological studies of primate retina suggest a similar diversity of ganglion cell types, 29 research has focused on the function of only a few cell types. In human retina, recordings 30 from individual cells are anecdota… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 68 publications
(109 reference statements)
0
8
1
Order By: Relevance
“…This study concluded that the human retina has a substantially greater diversity of functional cell types than macaque retina, and identified only ~5% of recorded cells that resembled parasol and midget cells, in striking contrast to the numerical dominance of midget and parasol cells in the present results and those of the other recent studies of human retina [12,13], as well as anatomical findings [8,28]. The unique conclusions of this recent study [14] may arise from technical factors. Cell type identification was not confirmed by quantitative clustering (Fig.…”
Section: Discussioncontrasting
confidence: 79%
See 2 more Smart Citations
“…This study concluded that the human retina has a substantially greater diversity of functional cell types than macaque retina, and identified only ~5% of recorded cells that resembled parasol and midget cells, in striking contrast to the numerical dominance of midget and parasol cells in the present results and those of the other recent studies of human retina [12,13], as well as anatomical findings [8,28]. The unique conclusions of this recent study [14] may arise from technical factors. Cell type identification was not confirmed by quantitative clustering (Fig.…”
Section: Discussioncontrasting
confidence: 79%
“…The third recent study [14] described responses of human RGCs to full-field stimuli with temporal frequency sweeps, full-field contrast steps, modulating gratings, and moving bars. A wide range of responses to these stimuli was observed, but quantitative cell type classification was not performed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The retina is designed to maximize total retinal information for the least cost [47]. To reveal the mechanism underlying the superb computational efficiency, much work has been devoted to understanding retinal neural codes [25,28,29,34,48,49]. Among several features, the heterogeneity of RGC spiking activities seems central for efficient coding [32][33][34][35][36][37], which better discerns different signals [28,29,34] and reduces the minimal number of cells to convey information [50,51].…”
Section: A How Does the Heterogeneity Matter For Artificial Vision?mentioning
confidence: 99%
“…This code is transmitted to postsynaptic targets in the brain, leading to visual perception. At present, more than 30 RGC types have been identified in the mouse retina [6], and between 15-20 types in the primate and human retina [7,8]. RGC classification is typically based on common anatomical features [9,10], responses to light [6,[11][12][13] or on shared gene expression [4,14,15].…”
Section: Introductionmentioning
confidence: 99%